Design guideline and conceptual design of dual polymer 3D printer nozzle - Quek, Hong Wei (2018)
This final year report aims to create a conceptual nozzle design for a dual-polymer blend composite 3D Fused Deposition Modelling printer. In this report, we will look into a general overview of 3D printing, the materials involved and the importance of developing a nozzle of this type. Two major concepts will be explored- Laser sintered composite printing and In-situ Blending. This project is in collaboration with the University of Luxembourg to further develop dual polymer blend FDM manufacturing for faster, safer and stronger products.